What Do We Know About the Global Financial Safety Net? A New Comprehensive Data Set - Beatrice D. Scheubel; Livio Stracca (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper critically reviews the theoretical basis for the provision of the global financial safety net (GFSN) and provide a comprehensive database covering four elements of the GFSN (foreign exchange reserves, IMF financing, central bank swap lines and regional financing arrangements) for over 150 countries in the sample period 1960-2015. This paper also presents some key stylised facts regarding the provision of GFSN financing and compares macroeconomic outcomes in capital flow reversal episodes depending on how much GFSN financing was available to countries. Finally, this paper concludes with some avenues for further research on the possible evolution of the GFSN.
Keywords: F32; F33; F34; G01; H87; 330; global financial safety net; financial integration; financial globalisation; IMF